Molecular characterization of the beta-adrenoceptor gene-family of rainbow trout (Oncorhynchus mykiss) - Nickerson, James G (University of Ottawa (Canada), 2003)
beta-Adrenoceptors (beta-ARs) are seven transmembrane domain, G-protein coupled receptors that transduce the cellular effects of the catecholamines, adrenaline (Adr) and noradrenaline (Nadr). Through their interaction with plasma membrane beta-ARs, catecholamines modulate a number of key physiological parameters aimed at allowing an organism to cope with environmental and physiological stressors. Mammalian species express three distinct beta-AR subtypes (beta 1-, beta2- and beta3-ARs) that exhibit complex modes of regulation and interaction. Relatively few studies have focused on beta-ARs from early branching vertebrates such as fish, particularly at the molecular level. The goal of this study was to characterize the beta-AR gene-family of the rainbow trout (RbT), Oncorhynchus mykiss. Three putative beta-ARs genes were cloned and a phylogenetic analysis predicted one beta2-AR subtype (RbT beta2-AR) and two beta3-AR subtypes (RbT beta3a- and RbT beta 3b-ARs) relative to the established mammalian beta-AR classification. The RbT beta2-, beta3a- and beta3b-AR genes code for proteins of 409, 427 and 477 amino acids, respectively. Hybridization of gene specific probes to trout tissue RNA indicated that RbT beta 2-AR was highly expressed in the liver, red muscle, and white muscle; RbT beta3a-AR was highly expressed in the gill and heart while RbT beta3b-AR was highly expressed in the blood. Pharmacological analysis indicated RbT beta2-AR binding characteristics consistent with mammalian beta2-ARs while the RbT beta3b-AR showed characteristics that were different from all known mammalian beta-AR subtypes. Differences in the potential regulatory phosphorylation profiles between trout beta-ARs suggests subtype specific sensitivities to the classic mechanisms of beta-AR desensitization. This molecular characterization of trout beta-ARs is the first study to demonstrate a beta3-AR homolog in fish, it identifies the trout red blood cell beta-AR as a beta3-subtype and provides support for the presence of a complex and unique beta-AR signaling system in the rainbow trout.
Keywords: Biology, Molecular.; Biology, Neuroscience.